Fahr's Sendromu: İki Olgunun Raporları - Şenoğlu, Mehmet; Tuncel, Deniz; Orhan, F.özlem; Yuksel, Zafer; Gokçe, Mustafa (Fırat University, 2007)
Fahr sendromu esas olarak ekstrapiramidal bulguların ve aynı zaman dametabolik, biyokimyasal, nöroradyolijik ve nöropsikiyatrik durumların birlikte prezente oldugu nadir bir klınik antitedir. Genellikle bilateralin trakraniyal kalsifikasyonlar insidental radyolijik bulgudur. Bu calışmada, biz iki fahr sendromlu olguyu literatur ışıgında tartışdık. Olgulardan birisi idiyopatik ve digeri hipoparatiroidizme sekonder oluşan olgu idi. Klinik olarak olgulardan biri nöbet ile ve digeri denge bozuklugu ile prezente oldu. Heriki hastanin kranial bilgisayarlı tomografisinde talamus, bazal ganglionlar ve serebellumda intrakranyaldiffuz bilateral kalsifikasyonlar mevcut idi. Fahr sendromu nadir karsılaşılan bir antite olmasına ragmen, anormal intrakraniyal kalsifikasyonlu vakaların ayırıcı tanısında diger familyal, konjenital ve metabolik hastaliklar ve sendromlar ile birlikte göz önünde bulundurulmalıdır. ©2007, Fırat Üniversitesi, Tıp Fakültesi

Fahr's syndrome is a rare clinical entity that presents mainly with extrapyramidal signs and accompanied with metabolic, biochemical, neuroradiological and neuro-psychiatric situations at the same time. Bilateral intracranial calcifications are usually encountered as an incidental radiological finding. In this study, we discuss two cases of Fahr's syndrome in the light of the literature; one of them idiopathic and the other one occurring secondary to hypoparathyroidism. Clinically, one of the cases presented with seizures and the other one with imbalance of the coordination system. Cranial computerized scans of both patients revealed intracranial diffuse bilateral calcifications in thalamus, basal ganglia and cerebellum. Fahr's syndrome, although encountered rarely, should also be taken into account in the differential diagnosis of cases with abnormal intracranial calcifications along with other familial, congenital and metabolic diseases and syndromes.©2007, Firat University, Medical Faculty
Fahr's Syndrome: A Report of Two Cases